Polymeric Micelles for Multidrug Delivery and Combination Therapy. Issue 38 (13th August 2013) - Aw, Moom Sinn; Kurian, Mima; Losic, Dusan
Abstract The use of conventional therapy based on a single therapeutic agent is not optimal to treat human diseases. The concept called "combination therapy", based on simultaneous administration of multiple therapeutics is recognized as a more efficient solution. Interestingly, this concept has been in use since ancient times in traditional herbal remedies with drug combinations, despite mechanisms of these therapeutics not fully comprehended by scientists. This idea has been recently re‐enacted in modern scenarios with the introduction of polymeric micelles loaded with several drugs as multidrug nanocarriers. This Concept article presents current research and developments on the application of polymeric micelles for multidrug delivery and combination therapy. The principles of micelle formation, their structure, and the developments and concept of multidrug delivery are introduced, followed by discussion on recent advances of multidrug delivery concepts directed towards targeted drug delivery and cancer, gene, and RNA therapies. The advantages of various polymeric micelles designed for different applications, and new developments combined with diagnostics and imaging are elucidated. A compilation work from our group based on multidrug‐loaded micelles as carriers in drug‐releasing implants for local delivery systems based on titania nanotubes is summarized. Finally, an overview of recent developments and prospective outlook for future trends in this field is given.